2012
DOI: 10.1002/jcb.24010
|View full text |Cite|
|
Sign up to set email alerts
|

Ca2+ store depletion and endoplasmic reticulum stress are involved in P2X7 receptor‐mediated neurotoxicity in differentiated NG108‐15 cells

Abstract: P2X7 receptor (P2X7R) activation by extracellular ATP triggers influx of Na(+) and Ca(2+), cytosolic Ca(2+) overload and consequently cytotoxicity. Whether disturbances in endoplasmic reticulum (ER) Ca(2+) homeostasis and ER stress are involved in P2X7R-mediated cell death is unknown. In this study, a P2X7R agonist (BzATP) was used to activate P2X7R in differentiated NG108-15 neuronal cells. In a concentration-dependent manner, application of BzATP (10-100 µM) immediately raised cytosolic Ca(2+) concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…As the principal organelle involved in Ca 2+ homeostasis, the ER tightly regulates Ca 2+ homeostasis in the ER lumen in order to maintain well protein folding and chaperone function [22,30]. Previous studies indicate that disturbance of intracellular Ca 2+ homeostasis induces ER stress and subsequent apoptosis associated with a variety of pathological conditions [21,[41][42][43]. We hypothesized that sustained dysregulation of intracellular Ca 2+ homeostasis plays a potential role in AGEs-induced ER stress and apoptosis in NP cells.…”
Section: Discussionmentioning
confidence: 98%
“…As the principal organelle involved in Ca 2+ homeostasis, the ER tightly regulates Ca 2+ homeostasis in the ER lumen in order to maintain well protein folding and chaperone function [22,30]. Previous studies indicate that disturbance of intracellular Ca 2+ homeostasis induces ER stress and subsequent apoptosis associated with a variety of pathological conditions [21,[41][42][43]. We hypothesized that sustained dysregulation of intracellular Ca 2+ homeostasis plays a potential role in AGEs-induced ER stress and apoptosis in NP cells.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the involvement of ER that form structural and functional networks with mitochondria, in the mitochondrial membrane permeabilization and apoptosis under various pathophysiological conditions, was suggested [97]. Moreover, it was previously demonstrated that ER stress is involved in P2X7R-mediated neurotoxicity in neuronal cells in the manner that is largely dependent from sustained Ca 2+ depletion from ER stores [98]. Since Ca 2+ released from ER is taken up by mitochondria that results in calcium overload and induces depolarization of mitochondrial membrane and opening of permeability transition pore (PTP) to release apoptotic proteins able to stimulate caspase cascade [99], it is though possible that P2X7R-mediated Ca 2+ release from ER might be responsible for mitochondria dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It was known that sustained elevation of [Ca 2+ ] i could induce some deleterious effect, for example, ER stress [17,32]. Ca 2+ overload causes dysfunction in ER Ca 2+ depletion, subsequently inducing accumulation of misfolded proteins in ER, this is termed unfolded protein response (UPR) [33].…”
Section: Discussionmentioning
confidence: 99%